Reducing Energy Requirements in Future Bioregenerative Life Support Systems (BLSSs): Performance and Bioactive Composition of Diverse Lettuce Genotypes Grown Under Optimal and Suboptimal Light Conditions - Rouphael, Youssef; Petropoulos, Spyridon A.; El-Nakhel, Christophe; Pannico, Antonio; Kyriacou, Marios C.; Giordano, Maria; Troise, Antonio Dario; Vitaglione, Paola; De Pascale, Stefania (Frontiers in Plant Science, 2019)
Space farming for fresh food production is essential for sustaining long duration space missions and supporting human life in space colonies. However, several obstacles need to be overcome including abnormal light conditions and energy limitations in maintaining Bioregenerative Life Support Systems (BLSSs). The aim of the present study was to evaluate six lettuce cultivars (baby Romaine, green Salanova, Lollo verde, Lollo rossa, red oak leaf and red Salanova) of different types and pigmentation under optimal and suboptimal light intensity and to identify the most promising candidates for BLSSs. Baby Romaine performed better than the rest of the tested cultivars under suboptimal light intensity, demonstrating a more efficient light harvesting mechanism. Stomatal resistance increased under suboptimal light conditions, especially in the case of Lollo verde and red oak leaf cultivars, indicating stress conditions, whereas intrinsic water use efficiency was highest in baby Romaine and red oak leaf cultivars, regardless of light regime. Nitrate content increased under suboptimal light intensity, especially in cultivars green Salanova and Lollo verde, while P and Ca accumulation trends were also observed in baby Romaine and Lollo verde cultivars, respectively. Chicoric acid was the major detected phenolic acid in the hydroxycinnamic derivatives sub-class, followed by chlorogenic, caffeoyl-tartaric and caffeoyl-meso-tartaric acids. Chicoric and total hydroxycinnamic acids were not affected by light intensity, whereas the rest of the detected phenolic compounds showed a varied response to light intensity. Regarding cultivar response, red oak leaf exhibited the highest content in chicoric acid and total hydroxycinnamic acids content under suboptimal light intensity, whereas red Salanova exhibited the highest hydroxycinnamic derivatives profile under optimal light conditions. The main detected carotenoids were β-cryptoxanthin and violaxanthin+neoxanthin, followed by lutein and β-carotene. All the target carotenoids decreased significantly under low light intensity, while red Salanova maintained a distinct carotenoids profile. Overall, cultivation of assorted lettuce cultivars is the optimal scenario for space farming, where baby Romaine could provide adequate amounts of fresh biomass owing to its high light use efficiency while red oak leaf and red Salanova could contribute to the daily dietary requirements for health-promoting bioactive compounds such as polyphenols and carotenoids.